Simple and interative access to biliodigestive anastomoses. - Girardi, Gino; Terra, Freddy; Langenhin, Raúl; Cura, Gabriel; Gajardo, Rubens; Tellechea (h), Miguel; Grillo, Bartolomé; Mayol, Ricardo (Cirugía del Uruguay, 1987)
A technical variation of biliodigestive anastomoses on jejunal Roux•in,Y loop is experimentaly avaluated. This variation enables easy access to the biliodigestive anastomoses with diagnostica! aims and the possibi• lity of therapeutical procedures guided by radiological or endoscopical methods under local anesthesy with no need of laparotomy.